3D Numerical Study on Magnetization Losses in Twisted Soldered-Stacked-Square (3S) HTS Wires Based on Homogenized Models. (July 2020) - Yao, L P; Lv, Y Y; Gu, F; Zhong, L H; Duan, X H; Song, M; Li, L; Li, Z Y; Hong, Z Y; Jin, Z J
Abstract: Magnetization loss is an important parameter in the application of high temperature superconductivity (HTS) power devices. In order to reduce magnetization losses, a novel soldered-stacked-square (3S) HTS wire with 1 mm width is firstly proposed and manufactured by our group. In previous work, numerical and experimental results have shown the magnetization loss in the 3S wire is one order smaller than that in the original 4 mm tape under perpendicular magnetic field. However, large eddy current loss and coupling loss will be generated under parallel field. Therefore, to further reduce the magnetization loss, the 3S wire has been twisted and investigated numerically in this paper. Firstly, two-dimensional (2D) numerical models are built for calculating the magnetization loss in untwisted 3S wires. To simplify the computation, a homogeneous bulk-like model is built which does not include the individual tapes of stack. The results show that the losses calculated by the homogenized model is similarly equal to the original results. Based on this, the homogeneous technique is further applied in three-dimensional (3D) numerical models of the twisted 3S wire. The results indicate that the homogenized model could make a good predict for the losses in twisted wires. What's more, the magnetization losses in twisted wires is compared with those in untwisted wires to verify that twisting process could actually reduce the magnetization loss of the novel superconducting wire.